Analisis Efektivitas Biaya Penggunaan Omeprazole atau Ranitidin pada Pasien Dispepsia di Instalasi Rawat Inap Salah Satu Rumah Sakit Swasta - Sinaulan, Evania A.; Nangoy, Edward; Masengi, Angelina S. R. (e-CliniC, 2025)
Abstract: Dyspepsia is a common condition that is commonly found in daily practice. The most common drugs for dyspepsia therapy are proton pump inhibitors (PPIs) and histamine-2 receptor antagonists (H2RAs). One of the factors that affects the cost of treatment that must be incurred by patients is the selection of treatment therapy. Pharmacoeconomic studies can compare the effectiveness of the two drug regimens in the treatment of dyspeptic patients. This study aimed to determine the effectiveness of therapy, average total cost, and cost effective value of the use of omeprazole or ranitidine therapy in dyspeptic patients at the Inpatient Installation of one Type C Private Hospital in Minahasa. This was a descriptive and observational study using the Cost-Effectiveness Analysis method with a retrospective data collection design in the period of January-June 2023. Based on medical record data of 72 patients, there were 30 patients using omeprazole and 42 patients using ranitidine. Ranitidine was more effective than omeprazole with the number of patients who reached the target therapy as many as 32 with a percentage of 76.1%. Ranitidine had a lower average total cost of therapy in dyspeptic patients which was Rp. 2,748,045 compared to omeprazole of Rp. 3,537,487. In conclusion, the use of ranitidine therapy in dyspepsia patients is more cost effective with Average Cost Effectiveness Ratio of Rp. 3,611,097. Keywords: dyspepsia; omeprazole; ranitidine; cost effectiveness analysis Abstrak: Dispepsia merupakan kondisi umum yang sering ditemukan pada praktek sehari-hari. Terapi dispepsia salah satunya adalah golongan proton pump inhibitors (PPIs) dan histamine-2 receptor antagonists (H2RAs). Salah satu hal yang berpengaruh pada biaya pengobatan yang harus dikeluarkan oleh pasien adalah pemilihan terapi pengobatan. Kajian farmakoekonomi dapat membandingkan efektivitas dua regimen obat tersebut dalam pengobatan pasien dyspepsia. Penelitian ini bertujuan untuk mengetahui efektivitas terapi, rata-rata biaya total, dan nilai cost effective dari penggunaan terapi omeprazole atau ranitidin pada pasien dispepsia di Instalasi Rawat Inap salah satu Rumah Sakit Swasta Tipe C di Minahasa. Jenis penelitian ialah deskriptif observasional menggunakan metode Cost-Effectiveness Analysis dengan rancangan pengambilan data secara retrospektif pada periode Januari-Juni 2023. Berdasarkan data rekam medis diperoleh 72 data pasien, terdiri dari 30 pasien yang menggunakan omeprazole dan 42 pasien yang menggunakan ranitidin. Ranitidin lebih efektif dibandingkan omeprazole dengan jumlah pasien yang mencapai target terapi sebanyak 76,1%. Ranitidin memiliki rata-rata total biaya terapi pada pasien dispepsia lebih rendah yaitu sebesar Rp. 2.748.045 dibandingkan omeprazole sebesar Rp. 3.537.487. Simpulan penelitian ini ialah penggunaan terapi ranitidin pada pasien dispepsia lebih cost effective dibandingkan omeprazole dengan nilai Average Cost Effectiveness Ratio yaitu Rp. 3.611.097. Kata kunci: dispepsia; omeprazole; ranitidin; analisis efektivitas biaya